How critical is "critical thinking"?. Issue 3 (2nd September 2016) - Strauss, Danie
Abstract : Before criticism is justified, an account of the applicable criteria should be given. This task concerns first of all the well-known logical principles of identity, contradiction and the excluded middle. They connect critical thinking to the conceptual element of rationality and to the normed nature of logical thinking, manifest in logically sound (norm-conformative) thinking and antinormative thinking—briefly also accounting for the dialectical tradition. An analysis of these principles requires an understanding of the uniqueness of, and coherence between, the logical and non-logical aspects in the light of contraries like logical-illogical, polite-impolite and frugal-wasteful. It also questions the idea of autonomy and examines the switch from principles to values. When a school of thought does not accept all the logical principles, the criteria for scientific thinking are challenged, for example in intuitionistic logic which rejects the universal validity of the principle of the excluded middle. It is then argued that the principle of sufficient reason and that of the excluded antinomy points at a more than logical foundation for critical thinking and ultimately calls for a non-reductionist ontology.